2016
DOI: 10.1016/j.cell.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Precision Tumor Recognition by T Cells With Combinatorial Antigen-Sensing Circuits

Abstract: SUMMARY T cells can be re-directed to kill cancer cells using chimeric antigen receptors (CARs) or T cell receptors (TCRs). This approach, however, is constrained by the rarity of tumor-specific single antigens. Targeting antigens also found on bystander tissues can cause life-threatening adverse effects. A powerful way to enhance ON-target activity of therapeutic T cells is to engineer them to require combinatorial antigens. Here we engineer a combinatorially activated T cell circuit in which a synthetic Notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
723
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 803 publications
(735 citation statements)
references
References 20 publications
8
723
1
3
Order By: Relevance
“…CAR-based (38,39) and synNotch/CAR AND gates (40) were designed to increase the safety of adoptive T-cells therapy by targeting only cells that display two cancer-specific surface markers. Nevertheless, it may also come at the risk of tumor cells escaping the treatment due to antigens heterogeneity and immunoediting.…”
Section: Discussionmentioning
confidence: 99%
“…CAR-based (38,39) and synNotch/CAR AND gates (40) were designed to increase the safety of adoptive T-cells therapy by targeting only cells that display two cancer-specific surface markers. Nevertheless, it may also come at the risk of tumor cells escaping the treatment due to antigens heterogeneity and immunoediting.…”
Section: Discussionmentioning
confidence: 99%
“…In these split constructs, antigen-binding and intracellular signaling components are separated without a dimerization agent, and then assembled together only in the presence of a heterodimerization-promoting small molecule, thus allowing one to precisely control the timing, location, and dosage of T cell activity for controlling potential toxicity [196]. Furthermore, several new designs of the CAR technology based on a synthetic Notch receptor system have been reported to enable T cell activation through recognition of combinational antigens, and to allow engineering of T cells with customized therapeutic response programs [197][198][199]. These studies illustrate the potential of combining cellular engineering with synthetic biology tools to produce safer therapeutic CAR-T cells for cancer immunotherapy.…”
Section: Car-engineered T Cell Immunotherapymentioning
confidence: 99%
“…Thus, while cancer vaccines using tissue-specific antigens or CT antigens such as MAGE-A3 are safe, but not potent enough to eradicate cancer, clinical studies using affinity-enhanced TCRs show the increased ability to recognize target tumor cells, but they also increase the risks of self-destruction of normal tissues or cross-reactivity against unanticipated targets expressed in essential normal tissues. For these reasons, it is better to include an inducible safety cassette or a regulatory switch in these TCR constructs, as demonstrated in CAR-based constructs [196,197,208].…”
Section: Tcr-engineered T Cell Immunotherapymentioning
confidence: 99%
“…41 Other elegantly designed logic-gate T cells have also been reported and some of them also require dual antigen recognition for CAR-T activation. 36,37 Our mCAR method offers one more strategy to create conditionally active CARs for enhancing tumor-specificity of CAR-T cells with less structural complexity.…”
mentioning
confidence: 99%
“…[36][37][38][39][40][41] One elegant strategy exploits dual targeting with two CARs to achieve selective recognition of tumor, but not normal cells. Sadelain and co-workers 38 demonstrated that T cells expressing two CARs targeting two different antigens could operate as logic gates to control full T cell activation.…”
mentioning
confidence: 99%